The Map of Healthtech in Indonesia As Database for Future Research - Dorien Kartikawangi; Hadi Saba Ayon (Ikatan Sarjana Komunikasi Indonesia, 2024)
The Covid-19 pandemic causes a lack of interaction among people. This situation forces digital transformation in many aspects of living, including health care. Helathtech then becomes a choice. This study explores Healthech in Indonesia with situation and organization analysis and provides a database for future research. A qualitative approach with secondary digital data is applied. The result shows twelve healthcare providers with different care focuses in Indonesia. They inform their service online through the official website and social media. Social media is also a means to build engagement with the audience, customer, and target market. Therefore, social media has become a marketing and public relations channel. Furthermore, there is a concern about data security regarding digital trace that opens in big data. Healthtech is called to take measures to ensure transparency and security of the data collected and to respect users' privacy. Protecting personal data produced and collected in this context must be ensured. Users must, therefore, be informed of the security procedures. By doing so, firms can develop a positive image and reputation. These tools can generate inequalities in treatment between the most advantaged people and others.